2018
DOI: 10.11124/jbisrir-2017-003487
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations and practices for the screening of depression and anxiety in acute coronary syndrome: a scoping review protocol

Abstract: The objective of this scoping review is to identify and map current recommendations and practices for the screening of depression and anxiety in acute coronary syndrome patients in the acute care setting.Specifically, the review questions are.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…5 All of the above factors may contribute to the pathogenesis of affective disorders in these patients, such as depression and anxiety. 6 Previous studies have confirmed that depression independently predicts poor clinical outcomes in patients with CAD. 7 However, the influence of anxiety on prognosis of CAD patients, particularly for those with ACS, is poorly understood.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…5 All of the above factors may contribute to the pathogenesis of affective disorders in these patients, such as depression and anxiety. 6 Previous studies have confirmed that depression independently predicts poor clinical outcomes in patients with CAD. 7 However, the influence of anxiety on prognosis of CAD patients, particularly for those with ACS, is poorly understood.…”
Section: Introductionmentioning
confidence: 94%
“… 5 All of the above factors may contribute to the pathogenesis of affective disorders in these patients, such as depression and anxiety. 6 …”
Section: Introductionmentioning
confidence: 99%